Community Empowerment Strategy as an Effort to Achieve Food Security Through Melon Picking Agrotourism - Sabani, Fajar; Turhamun, Turhamun (CV. Dyoqu Publishing Management, 2025)
Background: Food security is a crucial issue in Indonesia. Kebocoran Village, Banyumas, is developing melon-picking agrotourism as an innovative solution to address food security challenges and improve community well-being. Aims: This study aims to analyze the community empowerment strategies implemented by the Mina Pisang Farmers Group through the melon picking agrotourism program. Methods: This research is a field study using a descriptive qualitative approach. Primary data was obtained through interviews with farmer groups and village government officials. Data collection techniques used were observation, interviews, and documentation. Result: The integrated empowerment strategy uses the 5P approach (Enabling, Strengthening, Protecting, Supporting, and Maintaining). Enabling includes land access and melon cultivation training. Empowerment is carried out through technical training to increase farmer capacity. Conclusion: The Mina Pisang Farmers Group's 5P-based empowerment strategy has been successfully implemented. This program significantly strengthens village food security through land optimization, food diversification (melons), and simultaneously improves community welfare in a sustainable manner.